(untitled) (FULafia Journal of Science and Technology, 2023)
Microcytic-hypochromic anaemia was induced in Clarias gariepinus (Burchell, 1822) at intervals of 1, 7 and 14 days. Experimental fish were exposed to test water separately diluted with sub-lethal concentrations of paraquat of 0, 0.06, 0.07, 0.09 and 0.12mg/L. 14 days’ exposure to the sub-lethal concentrations of the toxicant resulted in mirocytic-hypochromic anaemia in the exposed fish. Blood indices attributable to mirocytichypochromic anaemia was observed with a significant (p<0.05) decrease in haemoglobin, haematocrit, red blood cells, Mean corpuscular volume (MVC), Mean corpuscular haemoglobin (MCH), Mean corpuscular haemoglobin concentration (MCHC), white blood cells, lymphocytes, monocytes, Neutrophils and eosinophil compared with the fish in the control test.